A Pilot Double‐Blind Randomized Trial of Perampanel for Essential Tremor. Issue 4 (31st March 2020) - Handforth, Adrian; Tse, Winona; Elble, Rodger J.
ABSTRACT: Background: Perampanel is a noncompetitive antagonist of alpha‐amino‐3‐hydroxy‐5‐methylisoxazole propionic acid glutamate receptors suggested to modulate tremor. Objectives: To assess the efficacy and tolerability of perampanel for essential tremor. Methods: This was a double‐blind, placebo‐controlled, randomized, cross‐over trial involving 26 patients titrated to 8 mg/day or a lower maximally tolerated dose as monotherapy or adjunct to antitremor medication. Tremor was assessed at the beginning and end of each 14‐week treatment arm. The primary endpoint was change in the videotaped performance subscale of The Essential Tremor Rating Assessment Scale, scored by a blinded rater. Secondary endpoints included change in The Essential Tremor Rating Assessment Scale Activity of Daily Living and Quality of Life in Essential Tremor and Subject Global Impression of Change subscales. Results: Data are available for 15 and 11 participants who completed placebo and perampanel arms, respectively. Perampanel was superior to placebo on the primary endpoint ( P = 0.028), Activity of Daily Living ( P = 0.009), and Subject Global Impression of Change ( P = 0.016), but not Quality of Life (p = 0.48). Video scores were rated >50% improved in 3/11 on perampanel and 0/15 on placebo. Adverse events were more likely on perampanel (especially at >4 mg/day) than on placebo, leading to withdrawal (36% vs. 10%) and dose reduction (41% vs. 15%). Adverse events more common with perampanel included imbalance/falls (50% vs. 10%), dizziness (36% vs. 10%), and irritability (27% vs. 5%). Conclusions: These findings suggest that perampanel exerts efficacy for some persons with essential tremor, but this population appears prone to adverse events.